Profesi Pengatur Belokan Jalan Dalam Perspektif Ekonomi Syariah (Studi Fenomenologi Di Persimpangan SMPN 2 Purwakarta) - Nurhayati, Rina; Suryana, Eka Ahadiyat; Suryadi, Aji (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2024)
Based on the results of the author's observations, the profession of road turn regulator does not have the legal auspices of the Constitution, in contrast to parking attendants who already have legal auspices under the guidance of the Department of Transportation of each city or region. The second phenomenon is the job security of the road turn regulator profession at the SMPN 2 Purwakarta Road Intersection, Kel. Ciseureuh Purwakarta has not been guaranteed, either health insurance or work accident insurance. The purpose of this study was to determine the profession of road turn regulator at the intersection of SMPN 2 Purwakarta in sharia economic perspective. This research uses qualitative methods with a phenomenological approach, data collection through observation, interviews with 5 respondents who have met the criteria, documentation studies. The results of the study can be concluded that